2019
DOI: 10.1051/matecconf/201926606012
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Analysis For Smart City Development Project: An Extensive Literature Review

Abstract: The current trend in urban planning has been evolved for developing the cities smart. Smart city concept directs urban development in to a strategic path to achieve sustainability in urban development. The understanding made up on the concept of smart city within any region would be fruitful to review in this nature. Similarly, the various stakeholders who would influence and contribute on smart city development projects are profound to identify in order to make the project success. As previous researches deno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 26 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Difficulties can be foreseen in balancing the need to increase stakeholders' engagement, while aiming to employ non-trivial strategies [241]. Nonetheless, there is evidence that stakeholders impact profoundly on energy planning scenarios [242,243]. Furthermore, stakeholders' views on MVEN and IES approaches were absent from the papers in our review, implying that this could be perceived as less relevant.…”
Section: Limits On Mven Cost and Benefits Analysismentioning
confidence: 94%
“…Difficulties can be foreseen in balancing the need to increase stakeholders' engagement, while aiming to employ non-trivial strategies [241]. Nonetheless, there is evidence that stakeholders impact profoundly on energy planning scenarios [242,243]. Furthermore, stakeholders' views on MVEN and IES approaches were absent from the papers in our review, implying that this could be perceived as less relevant.…”
Section: Limits On Mven Cost and Benefits Analysismentioning
confidence: 94%
“…This applies not only to the lack of financial resources, but also to the lack of expertise and staff. Jayasena et al, (2019) identified six strategies to overcome technology innovation challenges in the public sector in addition to the barriers. The researchers found that effective political strategy, the development of relevant policy, human capacity building, stakeholder management, effective communication, and private-public partnership are essential.…”
Section: Entrepreneurship and Municipal Collaborationmentioning
confidence: 99%
“…Urban projects usually involve more stakeholders than rural projects, such as urban planners, architects, community members, local authorities, etc. [56]. Using the framework in an urban setting should facilitate the integration of different perspectives and priorities in the assessment process.…”
Section: An Alternative Landscape Performance Measuring Frameworkmentioning
confidence: 99%